Words and Bots: An Empirical Experiment Vocabulary Mastery with Robotics in Young Children - Yuliani, Sri; Rizqiani, Diyah Ayu; Linarta, Arie (JOLLT Journal of Languages and Language Teaching, 2024)
This study aims to determine the impact of educational robot on increasing English vocabulary as a foreign language. Pre-experimental research design was conducted with 35 first grade junior high school students as sample. The pre-post English vocabulary test was given to the sample and the research were done in eight meetings. In the control class there was no action treatment and did not use robots in learning but in the treatment class, researchers used educational robots, namely the Evoce robot in learning. From the comparison between the two classes both the control class and the treatment class from the pre and post English vocabulary tests, the result finding showed in the t-test score based on the value of df = 35-1 = 34 at a significant level of 5%, a ttable of 1.0691 is obtained and at a significant level of 1%, a ttable of 2.441 is obtained. With a tcount of 9.899, which means that it is greater than ttable at a significance level of 5% and 1%, (1.0691 < 9.899 > 2.441) then Ho is rejected and Ha is accepted. In summary, the Evoce robot has given contribution in young learners’ English vocabulary. It recommended that the educational robot may become one of alternative media to be used for recent days for English vocabulary class.